1995
DOI: 10.1182/blood.v85.9.2490.bloodjournal8592490
|View full text |Cite
|
Sign up to set email alerts
|

Improved cytogenetics in multiple myeloma: a study of 151 patients including 117 patients at diagnosis

Abstract: Between December 1990 and January 1994, bone marrow (BM) samples from 151 patients with multiple myeloma (MM), including 117 patients evaluated at diagnosis, were collected for cytogenetic analysis. A total of 129 patients had assessable metaphases (100 patients at diagnosis). Cytogenetic studies were performed on BM cells after longterm cultures (6 days) with stimulation of cultures by granulocyte-macrophage colony-stimulating factor (GM-CSF), GM-CSF plus interleukin (IL)-6, IL-3 plus IL-6, or GM-CSF plus IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
47
0
6

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(63 citation statements)
references
References 36 publications
10
47
0
6
Order By: Relevance
“…We confirmed that the abnormality rate increased with the Durie and Salmon stage of the disease from 50% in stage I, to 62 . 5% in stage II and 94% in stage III, as well as with the evolution profile, but not with BM plasmacytosis (Weh et al, 1993;Lai et al, 1995;Smadja et al, 1995).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We confirmed that the abnormality rate increased with the Durie and Salmon stage of the disease from 50% in stage I, to 62 . 5% in stage II and 94% in stage III, as well as with the evolution profile, but not with BM plasmacytosis (Weh et al, 1993;Lai et al, 1995;Smadja et al, 1995).…”
Section: Discussionmentioning
confidence: 82%
“…The detection of aneuploid malignant PC by flow cytometry and fluorescence in situ hybridization in about 80% of patients (Zandecki et al, 1994;Drach et al, 1995), demonstrated that the 20-60% incidence of karyotypic abnormalities (Dewald et al, 1985;Gould et al, 1988;Gutensohn et al, 1992;Cigudosa et al, 1994;Lai et al, 1995;Sawyer et al, 1995) largely underestimated the frequency of genetic damage in MM (Zandecki et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical chromosomal abnormalities are common, 61-68% of patients show hyperdiploidy, 9-20% pseudodiploidy and 10-30% hypodiploidy . The most common abnormalities are trisomy 3, 7, 9 and 11 monosomy 13 and, in females monosomy X (Drach et al, 1995;Flactif et al, 1995;Lai et al, 1995;Tabernero et al, 1996). Recent data (Smadja et al, 1996) suggests that if patients are classified according to karyotype, those with hyperdiploidy may have a survival advantage.…”
Section: Cytogenetic and Molecular Variablesmentioning
confidence: 99%
“…Chromosome 14 abnormalities are common, with a reported frequency of 10-40% (Weh et al, 1993;Lai et al, 1995;Sawyer et al, 1995) and are associated with a poor prognosis, being seen mainly in stage III and the terminal phase of the disease (Liang et al, 1979;Philip et al, 1980). Translocations involving the switch region of the IgH gene on chromosome 14q have been characterized in cell lines.…”
Section: Cytogenetic and Molecular Variablesmentioning
confidence: 99%